0
$\begingroup$

Consider the following theorem:

Let $u: \mathbb{R}\rightarrow \mathbb{C}$, $u\in T$, the set of Laplace-transformable functions, and $v \in T$ as well, $v(t)=u(t)/t$. Then $\int^{\infty}_{s}\mathcal{L}\{u\}(\sigma)d\sigma=\mathcal{L}\{v\}(s)$ for $s \in \mathbb{R}$, $s>\lambda_u$, the abscissa of convergence of $u$.

One has, given $s \in \mathbb{C}$ with $\text{Re}(s)>\lambda_u$:

$\mathcal{L}\{u\}(s)=\mathcal{L}\{t$ $u(t)/t\}(s)= ${derivative of Laplace transform}$ =-\frac{d}{ds}\mathcal{L}\{u(t)/t\}(s)=-\frac{d}{ds}\mathcal{L}\{v\}(s)$.

This shows that $-\mathcal{L}\{v\}$ is a primitive for $\mathcal{L}\{u\}$ and therefore, by the complex version of the fundamental theorem of calculus, and for a sufficiently smooth curve $\Gamma: [a,b] \rightarrow \mathbb{C}$:

$\int_{\Gamma}\mathcal{L}\{u\}(z)dz= \mathcal{L}\{v\}(\Gamma(a)) - \mathcal{L}\{v\}(\Gamma(b))$ where $\Gamma(a), \Gamma(b)$ must of course fall in the domain of $\mathcal{L}\{v\}$. Choosing $\Gamma(a)=s$ (the same $s$ as above), and letting $\text{Re}({\Gamma(b)})\rightarrow + \infty$ one concludes (with a small change in notation for the integral) the following complex version of the theorem above:

Let $u: \mathbb{R}\rightarrow \mathbb{C}$, $u, v\in T$, $v(t)=u(t)/t$. Then $\int^{\infty}_{s}\mathcal{L}\{u\}(z)dz=\mathcal{L}\{v\}(s)$ for $s \in \mathbb{C}$, $\text{Re}(s)>\lambda_u$.

The argument still needs a proof of the existence of the integral $\int^{\infty}_{s}\mathcal{L}\{u\}(z)dz$, doesn't it?

However, is my reasoning correct or should I settle with the original version of the theorem?

Furthermore, in the original version $\sigma\in \mathbb{R}$, right?

Thanks in advance!

$\endgroup$
  • $\begingroup$ Let $U_T(s)=\int_0^Tu(t)e^{-st}dt,V_T(s)=\int_0^T \frac{u(t)}{t} e^{-st}dt$ assumed to converge absolutely (condition A). $U(s) =\lim_{T \to\infty} U_T(s),V(s) = \lim_{T \to\infty} V_T(s)$. If $\lim_{T \to\infty}U_T(s_0),\lim_{T \to\infty}V_T(s_0)$ converge (B) then integrating by parts $U(s_0+s) = \int_0^\infty U_t(s_0)s e^{-s t}dt,V(s_0+s) = \int_0^\infty U_t(s_0)(\frac{se^{-st}}{t}+\frac{e^{-st}}{t^2}) dt$ (no problem in $t=0$ by (A)) both converge absolutely for $\Re(s) > 0$ and $V'(s_0+s)=-U(s_0+s)$. Since $\lim_{\Re(s)\to \infty}V(s)= 0$ then $V(s)=\int_s^\infty U(z)dz$ $\endgroup$ – reuns Jan 11 at 15:04

Your Answer

By clicking "Post Your Answer", you acknowledge that you have read our updated terms of service, privacy policy and cookie policy, and that your continued use of the website is subject to these policies.

Browse other questions tagged or ask your own question.